A review on quinoline derivatives as anti-methicillin resistant Staphylococcus aureus (MRSA) agents - Pradeep Kumar (BMC Chemistry, 2020)
Abstract Methicillin Resistant Staphylococcus aureus (MRSA) consists of strains of S. aureus which are resistant to methicillin. The resistance is due to the acquisition of mecA gene which encodes PBP2a unlike of any PBPs normally produced by S. aureus. PBP2a shows unusually low β-Lactam affinity and remains active to allow cell wall synthesis at normally lethal β-Lactam concentrations. MRSA can cause different types of infections like Healthcare associated MRSA, Community associated MRSA and Livestock associated MRSA infections. It causes skin lesions, osteomyelitis, endocarditis and furunculosis. To treat MRSA infections, only a few options are available like vancomycin, clindamycin, co-trimoxazole, fluoroquinolones or minocycline and there is a dire need of discovering new antibacterial agents that can effectively treat MRSA infections. In the current review, an attempt has been made to compile the data of quinoline derivatives possessing anti-MRSA potential reported to date.